Principle and technology of step strengthening control of soft rock argillization roadway in coal mine - Guichen LI; Haoran HAO; Yuantian SUN; Jinghua LI; Sen YANG; Zeyu SHAO; Xiaofang WO (Meitan xuebao)
The sedimentary rock strata of the coal measure are generally characterised by significant argillity, high water content and weak lithology. The problem of controlling the stability of the surrounding rock in soft rock argillation roadways has become increasingly prominent. Taking the typical soft rock argillation roadway in Huaibei Mining area as the engineering background, based on the investigation and measurement of engineering geological conditions, the composition of clay minerals and the macro and micro failure characteristics are analyzed, and it is clear that the water-rich environment and stress environment are the important factors inducing the deformation and failure of argillation roadway. The mudification instability of surrounding rock is mainly reflected in the progressive failure mode of hydration of argillous rock mass, bearing failure of anchorage structure, and mud-state collapse of surrounding rock. It plays a decisive role to realize the stability control of bearing structure of surrounding rock in roadway under the coupling effect of stress-water. On this basis, the step strengthening control principle of soft rock argillation roadway is put forward. On the premise of ensuring the closed-loop structure with high preload, high stiffness and high strength anchor (cable) support in the interaction relationship between support and surrounding rock, the engineering instability control method is judged according to the hydration degree of mudstone. Three important technical paths have been formed to improve the properties of mudstone surrounding rock with anchor injection, strengthen the structure of shallow pile group with rotary grouting, and replace the mudstone mass with anchor injection layer by layer. The new multi-strand combined hollow grouting anchor cable bundle independently developed for mining is applied to the floor heave control in the west roadway of Luling Coal Mine. For the first time, the underground high pressure rotary-grouting engineering practice was carried out in the 8204 roadway of Guobei Coal Mine. The instability problem of mudded surrounding rock in belt roadway of the second level of Zhuxianzhuang Coal Mine is solved by the method of strong displacement of mudded surrounding rock by artificial constructed rock mass. According to the deformation of surrounding rock of roadway, the supporting forming condition of surrounding rock and drilling into results show that the results better solve the problem of soft rock roadway control. It strengthens the bearing capacity of surrounding rock of muddy roadway at multiple levels, ensures the long-term safety and stability of surrounding rock, and provides effective scientific control concept and technical support for surrounding rock control of soft rock argillation roadway.